(untitled) (Global Journal of Science Frontier Research, 2012)
The National Root Crops Research Institute (NRCRI), Umudike embarked on massive training and extension of technologies of new and improved food forms of root/tuber crops to rural farmers/women groups from 2005 to date in this country generally and in South-eastern parts in particular. However, the main purpose of this study is to determine the impact and adoption rate of the training/extension activity among farmers in Imo State of Nigeria. A structured interview schedule, administered to 90 farmers in 3 zones of Owerri, Orlu and Okigwe was the major instrument used in data collection. The respondents were 30 generated from a particular training point in each zone. The data were analysed using means, percentages and means scores. The result revealed that although the respondents were mostly women, an appreciable number of men participated in the training and these respondents were reasonably aware of the innovations. However, the adoptions of cassava innovations (value added and cultivation)by the respondents were near average but that of cocoyam and sweetpotato were very low.